Exit Profile of the School of Performing Arts, Reflecting on Its Mission - Hall Fernández, Wendy (2021)
This article describes a research process with the pedagogical aim of delving into the exit profile of graduates from the School of Performing Arts of Universidad Nacional, Costa Rica as a first approach to reflecting on and analyzing the school’s mission statement in terms of training professionals and the roles they can play after completing the major or graduating from it. Therefore, this research is focused on determining the employment situation of the population who completed the major or graduated from it. The research was developed during the period of 2017-2018, and it was systematized in 2019 as part of the pre-major project of the school. This process was carried out in a participatory way with the people who are current students, graduates, and staff from the School of Performing Arts, thereby following a reflection process on theater pedagogy which began in 2013 and continues to the present.